Recent developments in root canal treatment techniques in dental conservation: Perkembangan terkini teknik perawatan saluran akar dalam konservasi gigi - Purnamawati, Made Mega Indah; Dewi, Maya Sari; Hartini, I Gusti Agung Ayu (Makassar Dental Journal, 2025)
Root canal treatment (RCT) is an important procedure in dental conservation to preserve teeth that have undergone pulp infection or damage. This literature review examines the latest developments in RCT techniques, focusing on publications from the last five years. A systematic literature search was conducted using electronic databases with relevant keywords. The results show rapid advances in rotary instruments, minimally invasive preparation techniques, irrigation systems, obturation materials, and re-generative approaches. Imaging technologies such as CBCT and operating microscopes also contribute significantly to improving treatment success. It was concluded that the latest techniques in RCT have improved the efficiency, accuracy, and success rate of treatment, although long-term research is still needed to comprehensively validate the effectiveness.